PENGEMASAN PAKET EKOWISATA DI KABUPATEN BELITUNG PROVINSI BANGKA BELITUNG - Gantara, Helly; Sudana, I Putu; Eka Mahadewi, Ni Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 6 No 2 (2018): Jurnal IPTA (December 2018), 2018)
Belitung Regency is one of the most valuable holiday destinations, has a lot of natural potential that can be a new tour package to eliminate the saturation of tourists who will be there. The tour package is an ecotourism package, considering that in Belitung Regency. There are many ecotourism potentials such as: visiting the Mentas and Peramun Hills to see the typical flora and fauna cultivation of Belitung. Data collection techniques used in this study, interviews, documentation, and literature studies. The results of this study agreed that there were 10 destinations that became ecotourism packages. These potentials are packaged into 3 kinds of ecotourism packages in the form of tables, descriptions and graphs, namely, (1) Life of Tarsiers and Beautiful Mangrove Tourism, (2) Life of Beautiful Turtles and Coral Reef Tourism, (3) Exotic from Flora and Fauna on the Belitung Tour.